Distinct clonal evolution in a case with anaplastic embryonal rhabdomyosarcoma. Issue 7 (24th June 2021) - Kato, Keisuke; Yoshimi, Ai; Noda, Asami; Otani, Haruo; Hojo, Hiroshi; Tanaka, Mio; Tanaka, Yukichi; Ito, Yumi; Nishimura, Riki; Takita, Junko; Yanai, Toshihiro; Koike, Kazutoshi; et al.
Abstract: Background: Clonal evolution of malignancy is a complex process related to intratumoral heterogeneity, as recent studies have also demonstrated in rhabdomyosarcoma. The purpose of this study is to present a distinct clonal feature of a case with anaplastic embryonal type rhabdomyosarcoma (ERMS) using molecular analysis. Methods: A five‐year‐old girl developed a metastatic pelvic tumor. We cultured neoplastic cells isolated from the biopsy sample. Next, to characterize the current case, we analyzed the biopsy sample, autopsy sample, and established cell line using combined modalities, including histopathological, cytogenetic, and molecular assay. We also undertook the backtrack mutation‐specific polymerase chain reaction to reveal clonal composition. Results: The histology of the biopsy sample was consistent with ERMS with focal anaplasia. We established a permanently growing cell line, ICH‐ERMS‐1, from the biopsy sample. On molecular analysis, the biopsied tissue revealed a missense mutation at codon 245 of TP53 . In contrast, the autopsy tumor tissue and the cell line established from the biopsied tissue showed a missense mutation at codon 248. A backtrack study using mutation‐specific polymerase chain reaction detected a TP53 codon 248 mutation in the original biopsy sample. All the specimens examined had a missense mutation at PTPN11 codon 69. Conclusions: This study highlights intratumoral heterogeneity and distinct clonal change related to the functional context in our anaplastic ERMS case, supporting the concept of intratumoral heterogeneity and clonal evolution. It requires further case collection to reveal whether p14ARF–p53–MDM2 tumor suppressor pathway alteration, considered a late event in ERMS tumorigenesis, is responsible for anaplasia in ERMS.